PRESENTATIONAL TRAINING LECTURES ON NATURAL-SCIENCE DISCIPLINES: PRACTICE AND THEORY - Elena P. Bogomolova (Открытое образование (Москва), 2016)
This paper discusses the feasibility of delivering streaming lectures on natural-science disciplines with computer presentations. Typical students’ comments on those are observed. There are analyzed the strengths and weaknesses of this form of delivery of lecture material for students of full-time training.